Protective Role of Casuarinin from Melaleuca leucadendra against Ethanol-Induced Gastric Ulcer in Rats - Al-Sayed, Eman; Michel, Haidy E.; Khattab, Mohamed Abdelrazik; El-Shazly, Mohamed; Singab, Abdel Nasser (Planta Medica, 2020)
Gastric ulcer is a major health problem. Current treatment options of gastric ulcer, including antagonists of histamine H2 receptor and inhibitors of the proton pump, do not cure gastric ulcers, but only provide temporary relief of symptoms and can be associated with severe side effects. The lack of effective and safe medications for this global health problem urges for the discovery of novel classes of compounds with potent activity and an acceptable safety profile. Ethanol-induced ulceration in rats was used to evaluate the gastroprotective activity of casuarinin, an ellagitannin isolated from Melaleuca leucadendra. Casuarinin (25, 50, and 100 mg/kg) reduced the ulcer area by 45, 78, and 99%, respectively, compared with the ulcer group. Casuarinin (100 mg/kg) increased mucin content by 1.8-fold and reduced acidity by 42%. At the same dose, it also increased the levels of reduced glutathione by 194%, catalase by 586%, and prostaglandin E2 to its normal level. In contrast, it attenuated the ethanol-increased levels of malondialdehyde by 56%, TNF-α by 58%, and caspase-3 by 87%. Histological findings demonstrated that casuarinin exhibited a protective effect against tissue alterations in response to the ethanol-induced ulcer. Casuarinin suppressed the immunoexpression of nuclear factor-kappa B, cyclooxygenase-2, and inducible nitric oxide synthase to their normal values. It also induced the expression of heat shock protein-70, reaching up to 4.9-fold in comparison with the ulcer group. The potent gastroprotective effect of casuarinin was thus attributed to its anti-inflammatory, antioxidant, and antiapoptotic effects. Our results suggest the potential application of casuarinin as an antiulcer agent from natural sources.
Keywords: Melaleuca leucadendra; myrtaceae; caspase-3; COX-2; ellagitannins; casuarinin